2005
DOI: 10.1515/ijdhd.2005.4.2.59
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pain in adults with cognitive impairment: A review of the tools

Abstract: The aim of this paper is to discuss the results of a review into the literature related to chronic pain and the older adult. Several themes within the review have been identified and reported elsewhere and the final report has been published by the University of Sheffield in the form of an annotated bibliography. This report focuses upon the findings of the in relation to the assessment of pain in the adult with cognitive impairment. Issues surrounding assessment in the non-cognitively impaired older adult hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Furthermore, the qualitative literature suggests that older people link ageing to physical decline and being in pain, therefore they may be reluctant to seek help. This has also been found in the nursing home setting where, because older people believed their pain to be intractable, they often did not complain to staff (7). Some authors describe a process of normalisation where older women learn to 'get on with it' and develop their own management strategies.…”
Section: Impact Of Painmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, the qualitative literature suggests that older people link ageing to physical decline and being in pain, therefore they may be reluctant to seek help. This has also been found in the nursing home setting where, because older people believed their pain to be intractable, they often did not complain to staff (7). Some authors describe a process of normalisation where older women learn to 'get on with it' and develop their own management strategies.…”
Section: Impact Of Painmentioning
confidence: 96%
“…Attitudes of staff to pain in elderly people and effects upon management (7,16) Attitudes of staff Effects upon pain management…”
Section: Tablementioning
confidence: 99%
“…Works concerning their end of life are rare in French, although developed by English-speaking researchers (8,9), with studies about specific tools for the assessment of pain (10). Specialized gerontology for people with intellectual disability (ID) is also expanding, even though adapted practices are only at their beginning in France (6,11).…”
Section: Introductionmentioning
confidence: 99%
“…We identified 23 reviews as being potentially eligible for inclusion, of which 13 were excluded as they did not provide data on the psychometric properties of the tools. The remaining set included 10 records reporting data from eight reviews (the Schofield et al 2005 72 review was reported in three separate studies; [72][73][74] we have combined the results of this) ( Figure 3). The tables of included and excluded reviews are listed in Appendix 2.…”
Section: Data Extraction and Managementmentioning
confidence: 99%
“…The overall conclusion was that there is a need for further psychometric testing of each tool. Two reviews recommended that the focus should be on studying existing scales rather than creating new ones, 64,72 although one review also suggested that there may be a need to revisit the tools' conceptual foundations. 82 Recommendations for further research and testing of the tools included the involvement of culturally diverse populations 64,82,87 and the provision of scoring methods and guidelines for interpretation in the evaluation of the scale.…”
Section: Summary Of Findingsmentioning
confidence: 99%